Organocatalytic Enantioselective Conjugate Addition of Nitromethane to Benzylidene-2-Benzoyl Acetate: Asymmetric Synthesis of ABT – 627, an Endothelin Receptor Antagonist - Hajra, Saumen; Aziz, Sk Mohammad; Jana, Bibekananda; Hazra, Sunit (Frontiers in Chemistry, 2020)
First catalytic and enantioselective conjugate addition of nitromethane to benzylidene-2-benzoyl acetate has been developed using dihydroquinine derived squaramide catalyst with moderate to high selectivities. Asymmetric total synthesis of ABT-627, a potent ETA receptor antagonist is accomplished utilizing the developed method in overall 15.7% yield.